PEMANFAATAN GEOGEBRA DALAM PEMBELAJARAN MATEMATIKA: STUDI IMPLEMENTASI PBL DAN TPACK PADA MATERI DIMENSI TIGA - Muliadi, Handri; Adinda, Anita (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to evaluate the effectiveness of integrating GeoGebra in mathematicsinstruction through a Problem-Based Learning (PBL) model supported by the TechnologicalPedagogical Content Knowledge (TPACK) framework in teaching three-dimensional geometry. Theresearch subjects consisted of 30 twelfth-grade science students and three mathematics teachersfrom SMA Negeri 1 Sihapas Barumun, while the object of the study was the implementation processof GeoGebra-assisted learning. A mixed-methods approach with an explanatory sequential designwas employed, combining quantitative data (tests and attitude questionnaires) and qualitative data(observations and structured interviews). The results revealed a significant improvement in students'conceptual understanding, with average test scores increasing from 78.5 to 87.2. Additionally, therewas a positive shift in students' affective responses, including enhanced motivation and selfconfidence, as well as increased technical and collaborative skills. In conclusion, the integration ofGeoGebra within the PBL-TPACK framework effectively enhances spatial reasoning, learningengagement, and 21st-century skills in mathematics education.